AB0504 The Role of Corticosteroids in Rheumatoid Arthritis Patients Under Biologic Therapy. (9th June 2015) - Madureira, P.S.; Pimenta, S.; Vieira, R.; Fonseca, R.; Gonçalves, D.R.; Aguiar, F.; Rocha, T.; Bernardo, A.; Bernardes, M.; Costa, L.
Abstract : Background: Corticosteroids (CS) are used on rheumatoid arthritis (RA) treatment for decades, due to their rapid and efficacious improvement of arthritis. With the recent advances in RA treatment and the increasing awareness given to CS side effects it should be expected that these drugs started being used scarcely and for shorter periods of time. Objectives: Analyse the variations in CS dose in patients with RA after the start of biologic therapy. Analyse the existence of differences between biologics regarding CS therapy. Methods: A retrospective analysis of all patients with RA receiving biologic therapy of a rheumatology department of a Portuguese University Hospital. The demographic and clinic baseline data was collected. The variations in CS dose between baseline and 12 and 24 months were determined, as well as their difference according to the biologic agent: anti-TNF, Rituximab and Tocilizumab. Other biologics were excluded due to the small number of patients assigned to them. The proportion of patients steroid-free was determined as well as the differences according to the current biologic. All CS dose are displayed as the equivalent prednisolone doses. Results: In January 2015, 176 patients met the inclusion criteria; 88.3% were women, with mean age of 57.2 (±10.9) years, and disease duration of 19.8 (±9.8) years. Rheumatoid factor and/ or anti-cyclic citrullinated peptide (anti-CCP) were positive in 77.8% of patients. Mean baseline DAS28 was 6.02 (±1.41) and mean baseline HAQ was 1.80 (±0.56). Most of the patients (n=98) were treated with anti-TNF agents; 48 patients received rituximab and 30 tocilizumab. Mean CS dose at baseline was 7.02 (±4.33) mg/day; after 12 months of biologic therapy reduced to 6.29 (±3.93) mg/day (p<0.001) and after 24 months to 5.65 (±3.90) mg/day (p<0.001). With all the biologics analysed it was seen a significant reduction in steroids dose: in patients receiving anti-TNF agents mean CS dose reduced from 6.44 (±4.20) to 5.81 (±3.91) mg/day at 12 months (p=0.015) and to 5.48 (±4.01) mg/day at 24 months (p=0.002). With Rituximab it reduced from 7.74 (±4.42) to 6.55 (±3.54) at 12 months (p=0.032) and to 5.68 (±3.73) mg/day at 24 months (p=0.005); with Tocilizumab from 7.20 (±3.11) to 6.76 (±2.83) (p=0.136) and to 5.91 (±2.56) mg/day (p=0.043), respectively. We found a significant higher CS dose at 12 months of treatment in patients that switched biologic 2 or more times (7.50±4.59 mg/day) vs. patients that switched 1 time (6.23±2.65 mg/day) vs. patients that were being treated with their first biologic (6.14±4.19 mg/day) (p<0.001). The results were also significant different at 24 months. While at baseline only 8.9% of patients were steroid-free, this number increased to 10.7% at 12 months (p<0.001) and to 15.8% at 24 months (p<0.001). This effect was similar in anti-TNF agents (10.2%, 12.4% (p<0.001), 15.1% (p<0.001), respectively), Rituximab (8.3%, 10.4% (p=0.002), 20.0% (p<0.001), respectively). In tocilizumab this effect was less pronounced. Conclusions: This analysis suggests that RA patients can be maintained with low dose CS therapy for long periods, and that biologic therapies can contribute to decrease the dose of CS in these patients, and even allow a greater proportion of them to stop CS therapy. Disclosure of Interest: None declared